2020
DOI: 10.1101/2020.05.11.089185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SIFNet: Electromagnetic Source Imaging Framework Using Deep Neural Networks

Abstract: AbstractElectroencephalography (EEG) and magnetoencephalography (MEG) are used to measure brain activity, noninvasively, and are useful tools for brain research and clinical management of brain disorders. Tremendous effort has been made in solving the inverse source imaging problem from EEG/MEG measurements. This is a challenging ill-posed problem, since the number of measurements is much smaller than the number of possible sources in the brain. Various methods have been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…While various studies showed the strength and capability of such models to capture realistic brain dynamics, no prior work has employed these models to develop a noninvasive imaging and modeling framework and rigorously validated the results using ground truth, such as intracranial recordings and surgical resection outcomes in epilepsy patients. Our proposed deep learning framework ( 59 ) represents an effort at integrating biophysically inspired mesoscale models of neuronal activation, as embodied by NMMs, into DL-based ESI for distributed source imaging. The use of biophysically inspired brain network models for generating big training data represents an important undertaking as the performance, usability, and robustness of a neural network are based upon and bounded by the quality and nature of its training examples.…”
Section: Discussionmentioning
confidence: 99%
“…While various studies showed the strength and capability of such models to capture realistic brain dynamics, no prior work has employed these models to develop a noninvasive imaging and modeling framework and rigorously validated the results using ground truth, such as intracranial recordings and surgical resection outcomes in epilepsy patients. Our proposed deep learning framework ( 59 ) represents an effort at integrating biophysically inspired mesoscale models of neuronal activation, as embodied by NMMs, into DL-based ESI for distributed source imaging. The use of biophysically inspired brain network models for generating big training data represents an important undertaking as the performance, usability, and robustness of a neural network are based upon and bounded by the quality and nature of its training examples.…”
Section: Discussionmentioning
confidence: 99%
“…finding the neural sources given the signals measured on the scalp, is of major interest both for basic research and in the clinical context (e.g., localization of seizure onset zones in epilepsy). ANN-based analysis methods are gaining attention in the past years and appear a viable option to solve the inverse problem of the M/EEG (Cui et al, 2019; Dinh, Samuelsson, Hunold, & Hämäläinen, 2019; Hecker et al, 2020; Huang et al, 2020; Pantazis & Adler, 2021; Sun et al, 2020; Tankelevich, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the TBFs can not only increase the generalizability of the neural network but also reduce the complexity of the network training. SIFNet [28] also utilized a deep learning approach with data generation for the ESI problem, but there are three major differences between SIFNet and DST-DAE: 1) SIFNet only focuses on the single source estimation, while DST-DAE can estimate a multisource case; 2) SIFNet focuses on the source localization by reformulating the ESI problem as a classification problem, while DST-DAE further considers the regression of the temporal dynamics of the estimated sources; 3) SIFNet utilizes training signals corrupted with different SNRs to guarantee a modest denoising ability, leading to more sensitivity to the noise levels of the test samples, while DST-DAE has a superior and efficient denoising ability against different noise levels due to its denoising architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, deep neutal networks could be a potential new solution for the ESI problem. Recently, the source imaging framework network (SIFNet) [28] was proposed in an attempt to transform the ESI inverse problem into a supervised multiclassification task. After the brain source space is modeled as different interconnected regions, a residual-blockbased classification network can be succesfully trained using the generated training set, in which each training label is a one-hot vector representing the activation state of each region.…”
Section: Introductionmentioning
confidence: 99%